2016
DOI: 10.4172/2165-7556.1000168
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers Time Utilization Before and After the Introduction of an Electronic Nursing Documentation System in a Residential Aged Care Facility

Abstract: Background: Despite increasing research interest in caregivers' interaction with technology, there has been no attempt to investigate how the introduction of an electronic nursing documentation system in a residential aged care facility may affect caregivers' use of their time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…Staff perceptions of the influence of HIT on workflow were mixed: In some studies, staff described processes as more streamlined, 6,9,19,24,40,41 and in others, processes were more cumbersome. 7,16,18,25,27,30,32,42-44 In the quasi-experimental studies, staff in the intervention groups were more likely to report that documentation times and completeness improved. 8,41,42 In the studies that used direct observation and process mapping of workflows, the number of steps and the time to complete tasks were either reduced or the same with the new HIT system.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Staff perceptions of the influence of HIT on workflow were mixed: In some studies, staff described processes as more streamlined, 6,9,19,24,40,41 and in others, processes were more cumbersome. 7,16,18,25,27,30,32,42-44 In the quasi-experimental studies, staff in the intervention groups were more likely to report that documentation times and completeness improved. 8,41,42 In the studies that used direct observation and process mapping of workflows, the number of steps and the time to complete tasks were either reduced or the same with the new HIT system.…”
Section: Resultsmentioning
confidence: 99%
“…9,17,19,24,25,27 Of the studies that described training, many reported single sessions for nursing staff ranging from 30 minutes to 1 day, and single sessions for CNAs or personal care assistants (PCAs) of only 20 to 30 minutes. 9,19,21,24,29-31 In one of the few studies in which staff reported satisfaction with training, they received more training than what was typically reported: multiple days for nurses and full days for CNAs. 8 For new hires, training was often described as ad hoc, provided by other staff when available.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations